Long-acting relaxin analogues: a novel tool in cardiology - Wołowiec, Łukasz; Jaśniak, Albert; Osiak-Gwiazdowska, Joanna; Czaplińska, Daria; Szymczak, Agata; Pęcherz, Julia Anna; Grześk, Grzegorz (Frontiers in Pharmacology, 2025)
Serelaxin, a recombinant human relaxin, has emerged as a potential therapy for the future treatment of heart failure. However, its effectiveness has been limited by a short half-life and the need for intravenous administration. Recently developed long-acting relaxin analogues show promise in overcoming these limitations, as they exhibit an improved pharmacokinetic and pharmacodynamic profile while preserving the beneficial actions of relaxin. Their clinical utility has been confirmed in preclinical studies as well as in recently published first-in-human, randomized study focused on heart failure treatment (study ID: NCT04630067), and improvement of renal parameters in healthy volunteers (study ID NCT04768855). In this article, we provide an overview of the mechanisms underlying the effects of long-acting relaxin analogues and their positive impact on the cardiovascular system. Additionally, we present a comprehensive comparison between serelaxin and its novel analogues, exploring their potential implications for the future treatment of cardiovascular diseases.